Feasibility and potential cognitive impact of a cognitive-motor dual-task training program using a custom exergame in older adults: A pilot study - Gallou-Guyot, Matthieu; Mandigout, Stephane; Marie, Romain; Robin, Louise; Daviet, Jean-Christophe; Perrochon, Anaick (Frontiers in Aging Neuroscience, 2023)
Dual-task training may be relevant and efficient in the context of active ageing. An issue in training programs lies in enhancing the adherence of participants. This can potentially be improved using games as support. We designed and developed a custom interactive exergame in this way. The objective of this pilot study was to explore the potential use of this exergame and the feasibility of our intervention, including the level of safety and adherence. The result’s trends on cognitive and motor capacities, as well as on the level of motivation for physical activity, fear of falling and quality of life of participants were also explored. Older adults aged 65 or older were recruited, and realized 30 minutes of supervised training in groups of 4, 2 to 3 times a week for 12 weeks. Exercises consisted in incorporated cognitive and motor dual tasks, with an increased difficulty over the weeks. Our program’s safety, engagement, attendance, and completion levels were evaluated. Participants’ postural control in single and dual-task conditions, as well as their performances in mental inhibition, flexibility, working memory, mobility, postural control, and their levels of motivation for physical activity, fear of falling and quality of life were also assessed. We realized a per protocol statistical analysis with a p-value set at 0.05. Thirty-nine participants (84.6 ± 8.5 years old) were recruited. No adverse events, and 89% adherence, 88% attendance and 87% completion rates were observed, as well as a potential significant effect of our exergame on working memory in single task condition and on cognitive aspect of dual-task. We observed no differences in other parameters. Our exergame seemed feasible, safe, and enjoyed by participants, mainly due to the gamification of our training program. Moreover, our exergame may be efficient for cognitive training in older adults, as well as for the maintenance of motor functions, motivation for physical activity, fear of falling and quality of life levels. This constitutes a first step for our solution with interesting results that need to be further studied.